PhD research and study on operation and Business management by Iqbal shaukat - Iqbal Shaukat (Bussman Journal : Indonesian Journal of Business and Management, 2026)
The dream of prosperous economic growth and development is only possible through structured economic development. Industrial development forms a highly important part of this economic growth, and industrial growth is only possible with supply chain management. Operation management is an integral part of industrial development, boosting economic growth, and providing clear methods for the optimal utilization of the factors of production. Material management plays a dynamic role within operation management; by maintaining better material management models, production targets can be estimated and successfully achieved. Furthermore, procurement, purchasing, cost-volume analysis, and quality control management establish the crucial standards and principles needed to minimize resource costs and attain better production standards.